Guanabenz and Clonidine, α2-Adrenergic Receptor Agonists, Inhibit Choroidal Neovascularization - Tanaka, Miruto; Inoue, Yuki; Imai, Takahiko; Tanida, Norifumi; Takahashi, Koichi; Hara, Hideaki (Current Neurovascular Research, 2021)
Background: Neovascular age-related macular degeneration (AMD) with choroidal neovascularization (CNV) is a leading cause of blindness in elderly people. Anti-vascular endothelial growth factor (anti-VEGF)-drugs are used to treat AMD patients; however, some patients are resistant to these therapies. Objective: The purpose of this study was to investigate the anti-angiogenic effects of α2-adrenergic agonists, including guanabenz and clonidine. Methods: We evaluated the anti-angiogenic effects of α2-adrenergic agonists in human retinal microvascular endothelial cells (HRMECs). A proliferation assay was conducted, and the migration ratio was evaluated. In a laser-induced CNV model, guanabenz and clonidine were delivered via intraperitoneal injection or implantation of an osmotic pump device. Fourteen days following CNV induction, CNV lesion size and fundus fluorescein angiography (FFA) were evaluated. Results: Guanabenz and clonidine inhibited VEGF-induced retinal endothelial cell growth and migration. In the CNV model mice, CNV lesion sizes were reduced by intraperitoneal administration of guanabenz or clonidine. Data, including body weight, systolic blood pressure, and heart rate showed that guanabenz (0.5 and 2.0 mg/kg/day) had little effect on these parameters; conversely, a high dose of clonidine (1.0 mg/kg/day) did affect these parameters. Additionally, clonidine did not affect CNV size, but continuous administration of guanabenz attenuated both CNV size and leakage from neovessels. Conclusion: Our study suggests a key role for α2-adrenergic receptors during CNV formation. Therefore, we suggest that α2-adrenergic receptor agonists may represent novel therapeutic drugs for patients with neovascular AMD.
Keywords: vascular endothelial growth factor